MODERN APPROACHES TO THE DEVELOPMENT OF SMALL BUSINESS IN UKRAINE: CHALLENGES, TRENDS AND SUPPORT TOOLS (Development Service Industry Management, 2025)
The small business sector is crucial for shaping a competitive economy, creating new jobs, ensuring market adaptability, and stimulating regional development. In the context of the transformation of the Ukrainian economy, the growth of challenges caused by the military conflict, economic instability and changes in global market conditions, the issue of effective support and development of small business is of particular importance. Despite its significant potential, small businesses in Ukraine face many obstacles: limited access to financial resources, an unstable tax environment, bureaucratic procedures, weak institutional support, and a low level of digitalization. At the same time, recent years have shown new positive trends, including the intensification of state and international support programs, the development of the startup ecosystem, the use of digital platforms, and the adaptation of entrepreneurs to new realities through flexible business models. This makes it extremely relevant to study modern approaches to the development of small business, analyze the main challenges and opportunities, as well as study effective support tools for the formation of reasonable recommendations for improving state policy in the field of entrepreneurship and stimulating sustainable economic growth in Ukraine.Small business is a key element of the economic structure of Ukraine, providing significant employment of the population, making a significant contribution to the formation of the gross domestic product and promoting the introduction of innovations. The development of small business is of particular relevance in the context of economic instability, military conflict and global digital transformation, which requires entrepreneurs to be flexible, adaptable and actively use modern technologies. In recent years, Ukraine has seen an increase in the state and international strengthening of the small business sector, the expansion of the startup ecosystem, the spread of digital platforms and tools, which creates new opportunities for entrepreneurs. At the same time, small businesses face a number of serious problems, including insufficient access to financial resources, a complex system of taxation and state regulation, the consequences of martial law, as well as an unstable situation in domestic and foreign markets.Modern approaches to the development of small business in Ukraine are formed under the influence of large-scale internal and external challenges, among which the consequences of martial law, economic instability, logistical barriers and personnel losses occupy a special place. Despite this, small businesses demonstrate high adaptability and resilience, introducing digital technologies, flexible management models, innovations and expanding cooperation with international partners. At the same time, the state is actively involved in the process of supporting entrepreneurship, offering a wide range of financial, organizational, educational and digital tools. This creates conditions for the modernization of entrepreneurial activity, the growth of competitiveness and the development of the small business ecosystem as an important element of economic stability and recovery of the country. Therefore, in order to ensure the sustainable development of small business in Ukraine, effective cooperation between government agencies, the business environment and civil society is necessary, taking into account current trends and challenges.
Keywords: e-democracy; civic technologies; digital participation; local self-government; territorial communities; economic efficiency; public administration